Sensory Characteristics and Nutrient Content of Food Bar with Flour and Pumpkin Seed Substitution - Mutia Reski Amalia; Nuryani Nuryani; Budi Santoso (Sarana Ilmu Indonesia (salnesia), 2022)
The development of snack bar products from fruit and pumpkin seeds can provide health benefits. The purpose of this study was to assess the sensory characteristics and nutritional value of a food bar with flour and pumpkin seeds substitution. The research method used a completely randomized design with 3 treatments with different formulations of pumpkin flour and pumpkin seeds. Parameters observed included color, aroma, taste, texture, and proximate tests including moisture, protein, fat, ash, and carbohydrate content. The data from the level of preference test variables would be analyzed using the t-test. The results showed the organoleptic analysis of the highest color at F4 (2,55), preferred aspect taste at F1 (3,48), aroma at F1 (3,55), and texture at F2 (3,84). Proximate analysis was showed the highest in water content at F2 (20,14%), the ash content in F4 (2,77 g), protein content in F1 (18,65 g), fat content in F1 (22,48 g), the fiber content in F2, and carbohydrate content in F4 (42,15 g). The conclusion that there were significant differences in the sensory test of color, taste, and aroma from four food bar formulas with flour and pumpkin seed substitution, while the density (texture) of the food bar formulas was not significantly different from each other.